2016
DOI: 10.18632/oncotarget.9509
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-608 rs4919510 polymorphism and cancer risk: a meta-analysis based on 13,664 subjects

Abstract: Single nucleotide polymorphisms (SNPs) in MicroRNAs (miRNAs) are involved in the mechanism of carcinogenesis. Several studies have evaluated the association of rs4919510 SNP in miR-608 with cancer susceptibility in different types of cancer, with inconclusive outcomes. To obtain a more precise estimation, we carried out this meta-analysis through systematic retrieval from the PubMed and Embase database. A total of 10 case-control studies were analyzed with 6,000 cases and 7,664 controls. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…It has been proposed that rs4919510 C>G variant in miR-608 can alter its binding to target genes. MiR-608 expectedly targets growth hormone receptor (GHR), interleukin-1 alpha (IL1A), insulin receptor (INSR), and TP53[ 7 9 ]. Several studies examined the impacts of miR-608 rs4919510 C>G on breast cancers risks, but the results were inconsistent[ 8 , 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that rs4919510 C>G variant in miR-608 can alter its binding to target genes. MiR-608 expectedly targets growth hormone receptor (GHR), interleukin-1 alpha (IL1A), insulin receptor (INSR), and TP53[ 7 9 ]. Several studies examined the impacts of miR-608 rs4919510 C>G on breast cancers risks, but the results were inconsistent[ 8 , 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there are numerous reports describing cancer risk association with SNPs related to microRNAs life. In a meta-analysis by Liu and colleagues (Liu H. et al, 2017 ), conducted on ten studies with 6,000 cases and 7,664 controls, a significant association of miR-608 rs4919510 polymorphism with decreased cancer risk via recessive model (CC vs. GG + GC) was found. Interestingly, the same polymorphism has been already described to predict the clinical outcome in patients with different cancer types (Lin et al, 2012 ; Zheng et al, 2013 ; Pardini et al, 2015 ).…”
Section: Mirsnpmentioning
confidence: 99%
“…Several studies have shown the importance of single nucleotide polymorphisms (SNPs) for the risk of cancer development. Such SNPs are located either in genes involved in microRNA biogenesis or inside microRNA binding sites (MBS) at the target mRNA [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%